2016
DOI: 10.1371/currents.outbreaks.06d10b6b4e690917d8b0a04268906143
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Meningococcal Meningitis Serogroup C Outbreak in Northwest Nigeria, 2015 – Third Consecutive Outbreak of a New Strain

Abstract: BACKGROUND: In northwest Nigeria in 2013 and 2014, two sequential, localized outbreaks of meningitis were caused by a new strain of Neisseria meningitidis serogroup C (NmC). In 2015, an outbreak caused by the same novel NmC strain occurred over a wider geographical area, displaying different characteristics to the previous outbreaks. We describe cases treated by Médecins Sans Frontières (MSF) in the 2015 outbreak. METHODS: From February 10 to June 8, 2015, data on cerebrospinal meningitis (CSM) case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 15 publications
1
35
0
Order By: Relevance
“…This study analyses data collected during three sequential outbreaks of NmC in northern Nigeria in 2013 (9 February to 23 June; 856 clinically suspected patients treated), 2014 (14 March to 3 May; 333 cases), 5 and 2015 (10 February to 8 June; 6394 suspected cases 17 ). During these NmC outbreaks, Médecins Sans Frontières (MSF) managed treatment centres within existing Ministry of Health facilities in areas affected by the outbreaks: three sites in Sokoto state in 2013; one in Kebbi state in 2014; and two in Sokoto and five in Kebbi in 2015 ( Supplementary Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…This study analyses data collected during three sequential outbreaks of NmC in northern Nigeria in 2013 (9 February to 23 June; 856 clinically suspected patients treated), 2014 (14 March to 3 May; 333 cases), 5 and 2015 (10 February to 8 June; 6394 suspected cases 17 ). During these NmC outbreaks, Médecins Sans Frontières (MSF) managed treatment centres within existing Ministry of Health facilities in areas affected by the outbreaks: three sites in Sokoto state in 2013; one in Kebbi state in 2014; and two in Sokoto and five in Kebbi in 2015 ( Supplementary Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…8 NmC subsequently spread more widely causing endemic cases and epidemics across north Nigeria and neighboring Niger in 2015-2017 ( Figure 3B). 9,35,36,82 Niger and Nigeria each experienced over nine thousand suspected cases and over five hundred deaths due to NmC epidemics in 2015 and 2017, respectively. 9,35,36 NmC epidemics were characterized by very high attack rates in the range of 41.4-673 cases per 100,000 population, comparable to those seen during NmA epidemics.…”
Section: Capsular Group C Imdmentioning
confidence: 99%
“…9,35,36 NmC epidemics were characterized by very high attack rates in the range of 41.4-673 cases per 100,000 population, comparable to those seen during NmA epidemics. 8,9,82 Since 2013 NmC cases have also been recorded in Burkina Faso, Ghana, Benin and Mali suggesting wide regional spread of an epidemic strain. Molecular epidemiologic and whole genome characterization studies showed that epidemic NmC strains belonged to a newly identified ST-10217 lineage.…”
Section: Capsular Group C Imdmentioning
confidence: 99%
“…7 Outbreaks due to Neisseria meningitidis serogroup C (NmC) have also occurred but were smaller and less frequent than NmA outbreaks. 2,10 The last NmC outbreak in this region occurred in 1979 in Burkina Faso with 539 cases reported (attack rate (AR) 517/100,000). 7 Outbreaks caused by NmC in northern Nigeria are rare, with the last and only recorded outbreak in 1975 with no detailed report published.…”
Section: Outbreak Of Cerebrospinal Meningitis In Kebbi State Nigeriamentioning
confidence: 99%